A longitudinal examination of body‐checking behaviors and eating disorder pathology in a community sample of adolescent males and females. Issue 11 (19th August 2020) - Zaitsoff, Shannon L.; Pullmer, Rachelle; Coelho, Jennifer S.
Abstract: Objective: Related to the cognitive‐behavioral theory of eating disorders, body checking has gained increasing recognition as both a maintaining factor for eating disorders and an important target for treatment. However, it is unclear whether body‐checking behaviors contribute to the development of disordered eating, or if these behaviors develop as a response to experiencing eating disorder thoughts and behaviors. This study aims to examine the relationships between body‐checking behaviors and eating disordered thoughts and behaviors in adolescent females and males in the community over time. Methods: Participants included 238 adolescents ( n = 104 males, n = 134 females, M age = 16.5 years) recruited from high schools in British Columbia, Canada, who completed the Eating Disorder Examination Questionnaire and Body Checking Questionnaire at baseline (T1) and again approximately 4 months later (T2). Results: After controlling for baseline levels of eating pathology and body mass index (BMI), body checking at T1 predicted increases in eating pathology for both males and females. In contrast, after controlling for baseline levels of body checking and BMI, eating pathology at T1 did not predict changes in body checking for females, but it did for males. Findings suggest that, among adolescents, engaging in body‐checking behaviors may increase risk for disordered eating. Discussion: If supported by further research, targeting body‐checking behaviors in prevention programs may be warranted.